2010
DOI: 10.1111/j.1365-2249.2010.04114.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered natural killer (NK) cell frequency and phenotype in latent autoimmune diabetes in adults (LADA) prior to insulin deficiency

Abstract: SummaryApproximately 10% of the patients diagnosed with type 2 diabetes (T2D) have detectable serum levels of glutamic acid decarboxylase 65 autoantibodies (GADA). These patients usually progress to insulin dependency within a few years, and are classified as being latent autoimmune diabetes in adults (LADA). A decrease in the frequency of peripheral blood natural killer (NK) cells has been reported recently in recent-onset T1D and in high-risk individuals prior to the clinical onset. As NK cells in LADA patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 52 publications
2
46
1
2
Order By: Relevance
“…Although studies have reported no significant change in total B cells in peripheral blood of patients with T1D (21,24), little is known about B-cell subpopulations with distinct immune functions that may play a role in the diabetes spectrum of T1D, LADA, and T2D. We hypothesized that an altered phenotype of B-cell subsets is associated with autoimmune diabetes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although studies have reported no significant change in total B cells in peripheral blood of patients with T1D (21,24), little is known about B-cell subpopulations with distinct immune functions that may play a role in the diabetes spectrum of T1D, LADA, and T2D. We hypothesized that an altered phenotype of B-cell subsets is associated with autoimmune diabetes.…”
Section: Introductionmentioning
confidence: 93%
“…Considerable evidence shows that patients with autoimmune diabetes have altered frequencies of circulating immune cells, including T cells (19), dendritic cells (20), natural killer cells (21,22), and neutrophils (23). Although studies have reported no significant change in total B cells in peripheral blood of patients with T1D (21,24), little is known about B-cell subpopulations with distinct immune functions that may play a role in the diabetes spectrum of T1D, LADA, and T2D.…”
Section: Introductionmentioning
confidence: 99%
“…During the early phase of disease, individuals with LADA can retain good metabolic control through diet alone or by taking oral hypoglycemic drugs, and this state can last from months to years. However, a percentage of LADA patients progress toward insulin requirement, indicating that LADA involves a slow and progressive loss of b-cells (5), although the factors influencing this progression are not completely known (6). The first evidence, demonstrating that a high GADA titer is a stronger predictor of insulin requirement than a general GADA positivity, was obtained from two studies with a limited number of LADA patients (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…A study in humans showed that they are more frequent in the visceral adipose tissue and express higher levels of proinflammatory IFN␥ compared with the subcutaneous adipose tissue (13,42). NK cells are also involved in the development of latent autoimmune diabetes in adults and diabetes in nonobese diabetic mice (2,8) but have been suggested to be protective against the development of metabolic syndrome in obese humans (34). Studies using leptin receptor-deficient mice (db/db) have indicated that leptin is necessary for normal NK cell development (52).…”
mentioning
confidence: 97%